Host plant preference of Rhopalosiphum padi (Hemiptera: Aphididae) and its role in selecting crop border plants to reduce Potato virus Y (PVY) in seed potatoes - Kruger, Kerstin (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2014.